Evaluation of the Proximate Composition of Amsonia tabernaemontana Walt. Seeds and Glyceride Oil - Olga Teneva; Zhana Petkova; Ana Dobreva; Anatoli Dzhurmanski; Ginka Antova (Molecules)
The genus Amsonia, a member of the Apocynaceae family, comprises plants with notable medicinal benefits. In 2022 and 2023, Amsonia tabernaemontana Walt. seeds introduced to Bulgaria were collected and analyzed. Given the limited information available on the chemical composition of A. tabernaemontana, this study aimed to evaluate the phytochemical profile of the plant seeds collected over two consecutive years. Although members of the genus Amsonia are not conventional oilseed crops, the glyceride oil content was 7.8% and 11.1% in the respective samples. The chemical composition was meticulously analyzed, revealing carbohydrates in the largest amounts (60.4% and 61.3%), with crude fibers at 18.3% and 24.8%, and protein content at 19.5% and 13.0%. The amounts of ash and moisture content were also quantified. Additionally, the fatty acids, sterols, tocopherols, and phospholipids of the seed oil were examined. β-Sitosterol emerged as the main component in both harvests. The total tocopherol content was relatively low (52.7 mg/kg vs. 20.0 mg/kg), with α-tocopherol being predominant. Phosphatidylcholine, phosphatidylinositol, and phosphatidylethanolamine were identified as the principal components of the phospholipid fraction. The fatty acid composition primarily included linoleic (61.0 and 61.2%) and oleic acids (28.7 and 28.6%).